Our energy future introduction to renewable energy and biofuels - Jones, Carla S., 1981- (University of California Press, 2016)
"Our Energy Future is an introductory textbook for a college course in energy production, alternative and renewable fuels, and related issues involved in building a sustainable energy future. Our society is consuming energy at an alarming rate as trends in energy consumption continue to rise. Jones and Mayfield explore the creation and history of fossil fuels, their impact on the environment, and how they have become critical to our society. They warn that continuing fuel-usage patterns could permanently damage our environment. Jones and Mayfield also outline how the adoption of sustainable biofuels will be key to our future energy stability. They discuss a number of renewable energy options, and then discuss different biofuel feedstocks and their potential as replacements for petroleum-based products. This book emphasizes the importance of continued scientific, agricultural, and engineering development, while outlining the political and environmental challenges that are coupled with a complete shift from fossil fuels to renewable energy and biomass. Our Energy Future is an excellent, accessible resource for undergraduate students studying biofuels and bioenergy."--Provided by publisher.